PENERAPAN PEMBELAJARAN SOSIAL EMOSIONAL DENGAN MENGGUNAKAN TEKNIK STOP TERHADAP HASIL BELAJAR SISWA SMP MATERI EKOLOGI - Prasetyawan, Irvan Junaidi; Erman; Sulastri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the improvement in student learning outcomes through the use of Social Emotional learning by implementing the STOP method for Ecology material at SMP Negeri 1 Grogol. This research was carried out using a Classroom Action Research (PTK) approach which was carried out in two periods (cycles) where each period consisted of four levels, namely: planning, implementation, observation and reflection. The subjects in this research were 34 students in class VII C at SMP Negeri 1 Grogol. Data sources were collected from students, teachers, and documents. The data collection process was carried out through direct technical written tests. The results of this research show that the implementation of Social Emotional learning using the STOP Technique can improve student learning outcomes. This increase can be shown through the learning results for period (cycle) 1 with an average pre-test score of 48 having a learning completeness percentage of 3% and an average post-test score of 68 having a learning completeness percentage of 29%. Apart from that, for period (cycle) II, the average pre-test score was 79 with a learning completeness percentage of 65% and the average post-test score was 89 with a learning completeness percentage of 92%. Based on these results, it can be said that in cycle II, the student learning mastery indicator was achieved with a percentage of more than 85% with an average score above KKM≥75, so it can be said that the cycle was successful and stopped.